A Rare Case of Supinator Intramuscular Myxoma with Encasement of the Posterior Interosseous Nerve - Chiao Yee Lim; Suryasmi Duski; Ping Ching Chye (Case Reports in Orthopedics)
Intramuscular myxomas are rare, benign mesenchymal tumors. Tumor location in the forearm is very rare among all the intramuscular myxomas. To the best of our knowledge, there were two cases of supinator intramuscular myxoma reported in the literature, and we intend to report the third case of supinator myxoma with encasement of the posterior interosseous nerve (PIN). A 67-year-old lady presented with history of left proximal forearm swelling for the past 5 years. Magnetic resonance imaging showed a lobulated multiseptated lesion seen within left supinator muscle, which was hyperintense on T2-weighted images (T2WI) and hypointense on T1-weighted images (T1WI), with peripheral enhancement post contrast. The tissue diagnosis of myxoma was confirmed via an open biopsy. She underwent en bloc resection of the tumor. The PIN was encased by the tumor; it was preserved and carefully released from the tumor. The nerve sheath served as an excision margin. In conclusion, we present a rare case of an intramuscular myxoma in the supinator muscle. In view of the location, extra attention should be paid during excision surgery to locate the PIN and to avoid damaging the surrounding structures.